Flavor properties of post-heated fermented milk revealed by a comprehensive analysis based on volatile and non-volatile metabolites and sensory evaluation - Xiaoxia Li; Zhi Zhao; Shaoqi Shi; Dongdong Li; Yue Sang; Pengjie Wang; Liang Zhao; Fuqing Wang; Bing Fang; Shuxing Chen; Yixuan Li; Zhengqiang Jiang; et al. (Current Research in Food Science)
Existing research on the post-heating processing of fermented milk has primarily focused on single post-heating treatments and the texture, while research on how changes in metabolites during different post-heating treatments affect flavor and sensory properties is limited. This study investigates the changes in volatile metabolites in fermented milk treated at different post-heating temperatures to determine the characteristic aroma types and analyzes the changes in non-volatile metabolites associated with aroma-active compounds or their precursors to clarify the causes of the altered flavor and sensory properties. The results showed that in the 65 °C and 75 °C treatments, 63 volatile compounds were produced by Strecker degradation, lipid oxidation and esterification to produce ketones and aldehydes. Significantly higher odor activity values for 2,3-butanedione, hexanoic acid, and esters and significantly lower odor activity values for 2-heptanone enhanced the frankincense odors and creaminess of the post-heated fermented milk. With temperatures increasing to 95 °C, the increased ketones were primarily 2-heptanone, 2-nonanone, and 2-undecanone that originated from the oxidative decomposition of unsaturated phospholipids at high temperatures. The Maillard reaction of dipeptides produces nitrogenous heterocycles that trigger a caramelized flavor, while organic acids interact with proteins to form complexes that produce astringent flavors. These increase the oxidative off-flavors and reduce the overall palatability. These findings provide a scientific basis for optimizing the post-heating temperature process of fermented milk.